Answer:
Everyone would pay 116.66, but one of them would have to pay one cent extra!
Step-by-step explanation:
No,because a multiplcative inverse is when your changing a division or multiplcation sign!
Answer:
cos34°
sin56°
Step-by-step explanation:
Sin(2x+42)= sin90-(3x+13)
Sin(2x+42) = sin(90-13-3x)
Sin(2x+42) = sin(77-3x)
2x + 42 = 77-3x
5x. = 35
X = 7
If x = 7
cos(3x+13) = cos((3*7)+13)
cos(3x+13) = cos(21+13)
cos(3x+13)= cos34
And
sin(2x+42) = sin((2*7)+42)
sin(2x+42)= sin (14+42)
sin(2x+42) = sin56
Apples to oranges = 2 to 3
total ratio = 2+3=5
number Of apples = 2/5 * 45
= 2*9 =18
pls mark me as brainliest
The function, as presented here, is ambiguous in terms of what's being deivded by what. For the sake of example, I will assume that you meant
3x+5a
<span> f(x)= ------------
</span> x^2-a^2
You are saying that the derivative of this function is 0 when x=12. Let's differentiate f(x) with respect to x and then let x = 12:
(x^2-a^2)(3) -(3x+5a)(2x)
f '(x) = ------------------------------------- = 0 when x = 12
[x^2-a^2]^2
(144-a^2)(3) - (36+5a)(24)
------------------------------------ = 0
[ ]^2
Simplifying,
(144-a^2) - 8(36+5a) = 0
144 - a^2 - 288 - 40a = 0
This can be rewritten as a quadratic in standard form:
-a^2 - 40a - 144 = 0, or a^2 + 40a + 144 = 0.
Solve for a by completing the square:
a^2 + 40a + 20^2 - 20^2 + 144 = 0
(a+20)^2 = 400 - 144 = 156
Then a+20 = sqrt[6(26)] = sqrt[6(2)(13)] = 4(3)(13)= 2sqrt(39)
Finally, a = -20 plus or minus 2sqrt(39)
You must check both answers by subst. into the original equation. Only if the result(s) is(are) true is your solution (value of a) correct.